Please call again: Correcting non-response bias in treatment effect models - Luc Behaghel; Bruno Crépon; Marc Gurgand; Thomas Le Barbanchon (Institute for the Study of Labor (IZA), 2012)
We propose a novel selectivity correction procedure to deal with survey attrition, at the crossroads of the Heckit and of the bounding approach of Lee (2009). As a substitute for the instrument needed in sample selectivity correction models, we use information on the number of attempts that were made to obtain response to the survey from each individual who responded. We obtain set identification, but if the number of attempts to reach each individual is high enough, we can come closer to point identification. We apply our sample selection correction in the context of a job-search experiment with low and unbalanced response rates.
Keywords: C31; C93; J6; 330; survey non response; sample selectivity; treatment effect model; randomized controlled trial; Mikroökonometrie; Stichprobenverfahren; Befragung; Theorie; Arbeitsuche; Test